Bacterial Phototoxicity of Biomimetic Cdte-Gsh Quantum Dots - Vasquez-Guzman, C; Muñoz-Villagran, C (John Wiley and Sons Inc, 2021)
Aim: Fluorescent semiconductor nanoparticles or quantum dots (QDs) have excellent properties as photosensitizers in photodynamic therapy. This is mainly a consequence of their nanometric size and the generation of light-activated redox species. In previous works, we have reported the low-cost biomimetic synthesis of glutathione (GSH) capped QDs (CdTe-GSH QDs) with high biocompatibility. However, no studies have been performed to determine their phototoxic effect. The aim of this work was to characterize the light-induced toxicity of green (QDs500) and red (QDs600) QDs in Escherichia coli, and to study the molecular mechanism involved. Methods and Results: Photodegradation and reduction power of biomimetic QDs was determined to analyse their potential for radical generation. Escherichia coli cells were exposed to photoactivated QDs and viability was evaluated at different times. High toxicity was determined in E. coli cells exposed to photoactivated QDs, particularly QDs500. The molecular mechanism involved in QDs phototoxicity was studied by determining Cd2+-release and intracellular reactive oxygen species (ROS). Cells exposed to photoactivated QDs500 presented high levels of ROS. Cells exposed to photoactivated QDs500 presented high levels of ROS. Finally, to understand this phenomenon and the importance of oxidative and cadmium-stress in QDs-mediated phototoxicity, experiments were performed in E. coli mutants in ROS and Cd2+ response genes. As expected, E. coli mutants in ROS response genes were more sensitive than the wt strain to photoactivated QDs, with a higher effect in green-QDs500. No increase in phototoxicity was observed in cadmium-related mutants. Conclusion: Obtained results indicate that light exposure increases the toxicity of biomimetic QDs on E. coli cells. The mechanism of bacterial phototoxicity of biomimetic CdTe-GSH QDs is mostly associated with ROS generation. Significance and Impact of the Study: The results presented establish biomimetic CdTe-GSH QDs as a promising cost-effective alternative against microbial infections, particularly QDs500. © 2020 The Society for Applied Microbiology